Folate-Functionalized DNA Origami for Targeted Delivery of Doxorubicin to Triple-Negative Breast Cancer - Pal, Suchetan; Rakshit, Tatini (Frontiers in Chemistry, 2021)
DNA origami has emerged as a versatile platform for diverse applications, namely, photonics, electronics, (bio) sensing, smart actuator, and drug delivery. In the last decade, DNA origami has been extensively pursued for efficient anticancer therapy. However, challenges remain to develop strategies that improve the targeting efficiency and drug delivery capability of the DNA origami nanostructures. In this direction, we developed folate-functionalized DNA origami that effectively targets and delivers doxorubicin (DOX), a well-known anticancer drug to the folate receptor alpha (FOLR1) expressing triple-negative breast cancer (TNBC) cells in vitro. We show that folate-functionalized DNA origami structure targets and kills FOLR1 overexpressing cells with better efficacy than nontargeted origami. We envision that this study will open up the possibility of target specific delivery of anticancer drug combinations using the versatile DNA origami nanostructures to the drug resistant cancer cells.